Expanding the Role Repertoire While Aging: A Drama Therapy Model - Keisari, Shoshi (Frontiers in Psychology, 2021)
Drama therapy has been found to improve various facets of mental health while aging. It provides opportunities for personal growth and creative expression and enhances group relationships. Drama therapy is a widely acknowledged way to explore the life stories in late life. However, only a handful of studies have empirically explored the value of drama therapy for the aging population. This conceptual analysis was designed to address this need by developing a new integrative model of drama therapy. The analysis is based on the review of the results of four studies that explored the integration of life-review and playback theater as a drama therapy approach for older adults. The therapeutic process focused on the exploration of life-crossroads stories, a short unique technique, which enables the participants to craft a harmonious view of their life stories in a short-term dramatic creative group process. Combining the four results yielded a multidimensional model, which points to three potential transformative routes: the evolution of the life story, the evolution of improvised dramatic expression, and the expansion of social engagement. The transformative routes are described through the lens of role theory in drama therapy.